Variables that predict the appearance of burden in informal primary caregivers of children with cancer - Montero Pardo, Xolyanetzin; Jurado Cárdenas, Samuel; Méndez Venegas, José (Psicooncología, 2015)
The purpose of the study was to identify the psychological characteristics and care variables that predict the onset of primary informal caregivers burden (CPI) of children with cancer, in a hospital in Mexico City. The nonrandom sample consisted of 100 participants, who answered an integrated battery conformed by a health interview for the CPI, the load scale for the Zarit caregiver, the anxiety and depression of Beck inventory, the family support for the CPI scale and the scale modes of coping with stress by Lazarus and Folkman. The results confirmed that women react as CPI to children with cancer, and in most cases the patient’s mother. The variables of burden model stepwise multiple regressions were depression (R2=0.228), the number of affected areas in the caregiver’s life (R2=0.319) and anxiety (R2=0.348). In all the three variables explained 34% of variance. While coping style, family support, time to patient care, daily care hours and the number of activities carried out were not significant variables in predicting overload. The findings of this study could be useful for designing interventions that promote physical, social and emotional wellbeing of this population, preventing the patient from becoming caregivers.
Keywords: Children with cancer; caregivers; burden; anxiety and depression.